Limit theorems for conditional distributions with regard for large deviations - Zaigraev, A. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
Possible limit laws are studied for the multivariate conditional distribution of a subset of components of the sum of independent identically distributed random vectors under the condition that other components belong to the domain of large deviations. It is assumed that the considered distribution is absolutely continuous and belongs to the domain of attraction of the normal law but possesses “heavy tails.” The approach suggested is based on the local theorem for large deviations.